The Trail of the Bicentennial of the Liberal Triennium (1820-1823): Scientific Activity and Historiographic Production - Rújula, Pedro (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
The dates of the bicentenary of the period known in Spain as the Trienio Liberal (1820-1823) coincide, two hundred years later, with those of the covid-19 epidemic. Despite the difficulties for the development of scientific research, the commemorative activity has been intense, creating a community of historians who have debated the period and shed light on many subjects until now little known. This article offers a systematic review of all the scientific activity developed around Spain’s first peacetime constitutional episode, classifying and organising the different types of historiographical results and highlighting both its strengths and its grey areas.
Keywords: Liberal Triennium; historiography; bicentenary; political history; commemorations